Gliomatosis cerebri in children: A poor prognostic phenotype of diffuse gliomas with a distinct molecular profile - Nussbaumer, Gunther; Benesch, Martin; Grabovska, Yura; Mackay, Alan; Castel, David; Grill, Jacques; Alonso, Marta M; Antonelli, Manila; Bailey, Simon; Baugh, Joshua N; Biassoni, Veronica; Blattner-Johnson, Mirjam; et al. (Neuro-oncology, 2024)
BACKGROUND: The term gliomatosis cerebri (GC), a radiology-defined highly infiltrating diffuse glioma, has been abandoned since molecular GC-associated features could not be established. METHODS: We conducted a multinational retrospective study of 104 children and adolescents with GC providing comprehensive clinical and (epi-)genetic characterization. RESULTS: Median overall survival (OS) was 15.5 months (interquartile range, 10.9-27.7) with a 2-year survival rate of 28%. Histopathological grading correlated significantly with median OS: CNS WHO grade II: 47.8 months (25.2-55.7); grade III: 15.9 months (11.4-26.3); grade IV: 10.4 months (8.8-14.4). By DNA methylation profiling (n = 49), most tumors were classified as pediatric-type diffuse high-grade glioma (pedHGG), H3-/IDH-wild-type (n = 31/49, 63.3%) with enriched subclasses pedHGG_RTK2 (n = 19), pedHGG_A/B (n = 6), and pedHGG_MYCN (n = 5), but only one pedHGG_RTK1 case. Within the pedHGG, H3-/IDH-wild-type subgroup, recurrent alterations in EGFR (n = 10) and BCOR (n = 9) were identified. Additionally, we observed structural aberrations in chromosome 6 in 16/49 tumors (32.7%) across tumor types. In the pedHGG, H3-/IDH-wild-type subgroup TP53 alterations had a significant negative effect on OS. CONCLUSIONS: Contrary to previous studies, our representative pediatric GC study provides evidence that GC has a strong predilection to arise on the background of specific molecular features (especially pedHGG_RTK2, pedHGG_A/B, EGFR and BCOR mutations, chromosome 6 rearrangements).
Keywords: mutace; Neoplasms, Neuroepithelial; gliom; neuroepitelové nádory; Female; Phenotype; Infant; dítě; předškolní dítě; ženské pohlaví; Adolescent; nádory mozku; lidé; Neoplasm Grading; Mutation; následné studie; míra přežití; metylace DNA; Glioma; prognóza; retrospektivní studie; stupeň nádoru; Follow-Up Studies; Male; nádorové biomarkery; kojenec; Child, Preschool; DNA Methylation; Brain Neoplasms; Prognosis; Survival Rate; Biomarkers, Tumor; Child; fenotyp; mužské pohlaví; Retrospective Studies; mladiství; Humans